2009
DOI: 10.1007/s12237-009-9152-1
|View full text |Cite
|
Sign up to set email alerts
|

Whole Ecosystem Evidence of Eutrophication Enhancement by Wetland Dredging in a Shallow Tropical Lake

Abstract: The purpose of this research was to assess the effects of dredging performed in a marginal wetland colonized by aquatic macrophytes on eutrophication of the adjacent shallow tropical lake (Imboassica Lake, Brazil). The river mouth of the Imboassica River that drains into Imboassica Lake had been densely colonized by aquatic vegetation dominated by Typha domingensis (Pers.) when it was dredged. Total and dissolved nitrogen and phosphorus concentrations were measured monthly over 13 years at four stations in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…It has been shown that wetlands in the warm tropics are some of the most productive biological communities in the world (Neue et al, 1997), representing an important sink for nutrients (Marotta et al, 2009) and carbon (Peixoto et al, 2016;Sanders et al, 2017) as well as sources of organic substrates for carbon gas production in inland waters (Marotta et al, 2010). However, these wetland ecosystems are also highly threatened by land use activities, especially from deforestation, development of agricultural land and soil degradation (Junk, 2013;Lucas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that wetlands in the warm tropics are some of the most productive biological communities in the world (Neue et al, 1997), representing an important sink for nutrients (Marotta et al, 2009) and carbon (Peixoto et al, 2016;Sanders et al, 2017) as well as sources of organic substrates for carbon gas production in inland waters (Marotta et al, 2010). However, these wetland ecosystems are also highly threatened by land use activities, especially from deforestation, development of agricultural land and soil degradation (Junk, 2013;Lucas et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Despite similar TSS and nutrients in waters, St 60 showed a substantially lower pelagic GPP and phytoplankton biomass than St 30. The nutrient availability by sewage discharges (Marotta et al, 2009a) and absence of shading by riparian vegetation (Wallace et al, 1997) could stimulate the floating aquatic vegetation (e.g. S. auriculata), conditions that were observed in the Imboassica Stream after dredging.…”
Section: Discussionmentioning
confidence: 99%
“…The Imboassica Stream (22º 25' S e 42º 55' W) is a small fourth order tropical stream with low flow and about 14 km in length, the main tributary of the Imboassica Lagoon watershed (area = 55 km 2 ; Marotta et al, 2009a) in the North of Rio de Janeiro state (Southeast of Brazil, Figure 1). The low flow of this stream reflects the low altitudinal gradient from the spring to the mouth, as 90% of the extension is between 0 and 40 m (maximum altitude 120 m).…”
Section: Study Areamentioning
confidence: 99%
See 2 more Smart Citations